Breaking the silence surrounding childhood sexual abuse: consequences for our practice and selves as teacher educators. Issue 4 (4th July 2018) - Ramirez, Laurie A.; Allison, Valerie A.
Abstract: This collaborative self-study describes the efforts and consequences for two teacher educators including childhood sexual abuse (CSA) as a topic in their respective preservice courses. Survivors of CSA, the authors engaged in their instructional practices to promote greater awareness among their students of the prevalence of CSA and to encourage students to recognize the ethical versus legal dimensions of supporting survivors within the context of future practices. The authors, aided by two critical friends, found they came to greater understandings of themselves, personally and professionally, as a result of the collaborative self-study and concluded acknowledging their identities as CSA survivors was a powerful instructional strategy. Informed by social justice and advocacy literature, this study endeavors to prompt teacher educators and classroom practitioners to engage in open dialogue of a topic that has far-reaching personal and social consequences but has long been silenced.